Observational evidence confirms modelling of the long-term integrity of CO2-reservoir caprocks - N. Kampman (Nature Portfolio, 2016)
Anthropogenic CO2 storage, where CO2 is injected into saline geological resevoirs, relies on an impermeable caprock to seal in the CO2, but caprock reaction rates to CO2 acid brines are unclear. Here, Kampman et al. show that mineral reaction front alteration in caprocks takes place over 100,000 years.